A Shift From the Problematic of "Transformation". (25th March 2022) - Cockshott, Paul; Zachariah, David
Abstract : We examine the paradigm shift from that of the transformation model to that of stochastic profit models. Some of the anomalies undermining the transformation model are given graphically. In the last two sections we present volume II of Capital as an alternative starting point for thinking about the relation between value and price.